Mental health and wellbeing of medical students in Nigeria. A systematic review (2019)
In additional peculiar contemporary social problems due to income inequality, poverty, insecurity and political instability. These have a direct impact on their mental health and wellbeing. The aim of this study was to systematically review articles reporting on the epidemiology of psychiatric disorders among medical students in Nigeria. Studies were identified using MEDLINE, HINARI, African Journal Online (AJOL) and Google Scholar databases using search terms encompassing psychiatric morbidity amongst medical students. No date restrictions were applied to the search. The pooled prevalence estimate was calculated for each disorder. Psychological dis tress was present in 25.2% of the students, perceived stress in 60.5%, depression in 33.5% and anxiety in 28.8%. The current use of at least one psychoactive substance was present in up to 44.2%, while 35.5% of all the respondents had experienced one or more forms of abuse during their training as medical students. The prevalence of psychiatric disorders among medical stu dents in Nigeria is high. Positive coping mechanisms such as religiosity, positive reframing and resilience which were identified in this review should be optimized to reduce the burden.